The European Concerted Action on Anticoagulation (ECAA): Field Studies of Coagulometer Effects on the ISI of ECAA Thromboplastins - Poller, L.; van den Besselaar, A. M. H. P.; Jespersen, J.; Tripodi, A.; Houghton, D.; on behalf of the ECAA by the above steering committee (Thrombosis and Haemostasis, 1998)
Local calibration studies have been performed with lyophilized plasmas at 155 European laboratories to assess coagulometer effects on manual ISI of ECAA thromboplastins (low ISI human recombinant and high ISI rabbit brain). Common sets of 7 normal and 20 artificially depleted lyophilized plasmas were tested with the thromboplastins in the routine local coagulometers. With the human reagent, marked lowering of the manual ISI resulted with most coagulometers, which was associated with disproportionate shortening of the normals. Where this shortening did not occur, there was little coagulometer effect on the ISI. With the rabbit reagent, proportionate shortening with both normal and abnormal plasmas occurred in most instruments with little effect on ISI. INR correction by local ISI assignment appeared successful with the ECAA human reagent. There was negligible INR correction from local calibration of the ECAA rabbit reagent in coagulometers where thromboplastin ISI were unchanged from the ECAA established manual values.